Paeoniflorin và benzoylpaeoniflorin phân lập từ cây bạch thược (Paeonia lactiflora Pall.) - Kiệm, Phan Văn; Yến, Phạm Hải; Nhiệm, Nguyễn Xuân; Tùng, Nguyễn Hữu; Quang, Trần Hồng; Minh, Châu Văn (Vietnam Journal of Chemistry, 2014)
From the methanolic extract of the roots of Paeonia lactiflora Pall. two monoterpene derivatives paeoniflorin and benzoylpaeoniflorin were isolated. Their structures were identified based on the ESI and NMR (1D- and 2D-NMR) spectra in comparison with the previous reported data.